New reconstruction of DAN5 cranium (Gona, Ethiopia) supports complex emergence of Homo erectus - Baab, Karen; Kaifu, Yousuke; Freidline, Sarah; Rogers, Michael; Semaw, Sileshi (Nature Communications, 2025)
The African Early Pleistocene is a time of evolutionary change and techno-behavioral innovation in human prehistory that sees the advent of our own genus, Homo, from earlier australopithecine ancestors by 2.8-2.3 million years ago. This was followed by the origin and dispersal of Homo erectus sensu lato across Africa and Eurasia between ~ 2.0 and 1.1 Ma and the emergence of both large-brained (e.g., Bodo, Kabwe) and small-brained (e.g., H. naledi) lineages in the Middle Pleistocene of Africa. Here we present a newly reconstructed face of the DAN5/P1 cranium from Gona, Ethiopia (1.6-1.5 Ma) that, in conjunction with the cranial vault, is a mostly complete Early Pleistocene Homo cranium from the Horn of Africa. Morphometric analyses demonstrate a combination of H. erectus-like cranial traits and basal Homo-like facial and dental features combined with a small brain size in DAN5/P1. The presence of such a morphological mosaic contemporaneous with or postdating the emergence of the indisputable H. erectus craniodental complex around 1.6 Ma implies an intricate evolutionary transition from early Homo to H. erectus. This finding also supports a long persistence of small-brained, plesiomorphic Homo group(s) alongside other Homo groups that experienced continued encephalization through the Early to Middle Pleistocene of Africa. The origin and dispersal of Homo erectus, a long-lived and geographically widespread human ancestor, are unclear despite a rich fossil record. Here, the authors reconstruct the face from a Homo erectus cranium from Gona, Ethiopia, dated to 1.5-1.6 million years ago, providing insights into the evolutionary transition from early Homo to H. erectus.
Keywords: Crania; Early Pleistocene; Hominidae; Homo erectus; Human evolution; Pleistocene; Sensu; Skull; dept.ant

Imposed Form in the Early Acheulean? Evidence from Gona, Afar, Ethiopia - Stout, Dietrich; Liu, Cheng; Muller, Antoine; Rogers, Michael; Semaw, Sileshi (Journal of Archaeological Method and Theory, 2025)
Keywords: Acheulean; Ancient history; Anthropology; Archaeology; Early Stone Age; Ethnology; Geography; Handaxe; History; Large cutting tool; Lithic technology; Pick; Pleistocene; Shaping; Sociology; dept.ant

Seeking Transcendence: The Quest for Spirituality in an Age of Detachment - Manzella, Joseph C. (Routledge, 2025)
Seeking Transcendence examines the various paths taken by those who have detached themselves from their traditional, institutional religious roots but are seeking non-traditional paths to spiritual experiences. Called the “nones” or "non-affiliated" in popular mass media, these include a significant number of Western folks who maintain a belief in God or at least consider themselves “spiritual but not religious”. Each chapter of the book explores these trends with a specific theme, as well as a case study based on the author’s ethnographic observation of alternative spiritual communities and practices in North America and Western Europe. Ultimately, this book shows how contemporary alternatives to traditional institutional religion appeal to nones, presenting the relevance of new religious movements and more secular spiritual paths to transcendence.
Keywords: Philosophy; Psychoanalysis; Psychology; Theology; Transcendence (philosophy); dept.ant

Long-term hominin preference for the gallery forest edge: Insights from the Gona paleosols, Afar, Ethiopia - Stinchcomb, Gary E.; Rogers, Michael J.; Semaw, Sileshi (Quaternary Science Reviews, 2025)
The Gona Paleoanthropological Research Project area in the Afar Region of Ethiopia arguably contains one of the most complete records of archaeological sites anywhere in the world, from the earliest Oldowan dated to 2.6 Ma, to the Later Stone Age (LSA) dated to ca. 12-7 Ka. This makes Gona an ideal place to examine long-term trends in hominin-environment interaction. We revisited archaeological and hominin fossil sites at Gona and characterized the fossil soils using paleopedology and found evidence of paleo-Fluvisols, -Cambisols and -Vertisols. Greater than 70% of those archaeological sites spanning Oldowan to the Later Stone Age are found in buried paleosols with A-C and A-Bk-C paleosol profiles resembling modern-day Fluvisols or Fluvic Cambisols. Fluvisol morphology shows presence of bedding, incipient soil structure development and overprinting after burial. Stratigraphy and lithofacies show that these paleo-Fluvisols were proximal to the ancestral Awash River (Type I depositional system) or a distal fan channel (Type II depositional system). These data suggest that soil burial rates were rapid due to proximal flooding, where this would be a primary factor inhibiting soil development. This style of sedimentation and weathering resembles a narrow (5–10 m width) strip of land in a modern-day channel shelf and bar setting, separating the river from the adjacent gallery forest. A review of the literature shows that the frequent association of artifacts with paleo-Fluvisols may be prevalent throughout eastern Africa and indicates a long history of hominin reliance on a riverine ecosystem edge, proximal stream water and gallery forest resources within broader river valleys. The few older archaeological sites (e.g., Oldowan and Acheulian) found in/on more well-developed paleosols at Gona are an exception to this rule. These latter sites may hint at different land-use patterns and thus differing trajectories of hominin-environmental interactions. Because most paleosol studies at Gona and elsewhere in eastern Africa use paleo-Vertisols or other more well-developed calcareous soils to reconstruct paleoenvironment, there is a potential spatial and temporal decoupling between those well-studied paleosols and the more weakly-developed ones where archaeology is found.
Keywords: Archaeology; Artificial intelligence; Astronomy; Computer science; Enhanced Data Rates for GSM Evolution; Geography; Geology; Gona; Mathematics; Paleoecology; Paleontology; Paleosol; Physics; Preference; River corridors; Statistics; Term (time); dept.ant; peer-reviewed